Timing of FSH-stimulation and follicular development in cryopreserved human ovarian grafts - Van den Broecke, Rudy; Liu, Jun; Van der Elst, Josiane; Dhont, Marc (Reproductive biomedicine online, 2002)
Cryopreserved human primordial follicles grafted into immunodeficient hosts are susceptible to gonadotrophic stimulation but the optimal interval between grafting and stimulation has not been determined. The effect of stimulation with FSH at different time intervals after grafting was therefore investigated. Cryopreserved human ovarian cortical grafts from an androgen pre-treated female-to-male transsexual patient were transplanted into four groups of four non-obese, diabetic severe combined immune deficiency (NOD-SCID) mice. Ten, 12, 14 and 17 weeks after grafting, stimulation was started with daily intra-peritoneal injections of 5 IU of recombinant FSH for 14 days. Grafts were recovered and serially sectioned for counting the number of follicles and determining the different stages of development. Significantly more primary and secondary follicles were found in all stimulated groups compared with the non-stimulated control. This progression from the primordial to growing primary and secondary stages was most significant in the 14 weeks interval group. Formation of antral follicles was scarce and was only noticed in the 10 and 17 week groups. Cystic follicles and follicles with structural oocyte abnormalities were encountered in each group. Whether this phenomenon is related to the hormonal state of the tissue donor or to the cryopreservation and transplantation procedures is the subject of further investigation. It is concluded that the interval between grafting of ovarian tissue and the start of gonadotrophic stimulation may be important for an optimal follicular development after grafting.